2020
DOI: 10.1097/ccm.0000000000004210
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Cost-Utility of Critical Care and Subsequent Health Care: A Multicenter Prospective Study*

Abstract: Objectives: The number of critical care survivors is growing, but their long-term outcomes and resource use are poorly characterized. Estimating the cost-utility of critical care is necessary to ensure reasonable use of resources. The objective of this study was to analyze the long-term resource use and costs, and to estimate the cost-utility, of critical care. Design: Prospective observational study. Setting: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…There are limited data on cost‐utility of ICU treatment in general and even more so for COVID‐19. In a recent Finnish study [ 23 ], the costs per QALY for ICU treatment averaged £6367 ($7789; €7600), which was comparable to the costs per QALY of our study (£7511; $9179; €8969). Different countries use limit ranges for cost‐effectiveness of medical measures.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…There are limited data on cost‐utility of ICU treatment in general and even more so for COVID‐19. In a recent Finnish study [ 23 ], the costs per QALY for ICU treatment averaged £6367 ($7789; €7600), which was comparable to the costs per QALY of our study (£7511; $9179; €8969). Different countries use limit ranges for cost‐effectiveness of medical measures.…”
Section: Discussionsupporting
confidence: 81%
“…Intensive care treatment costs are disproportionally high, considering ICU beds make up less than 10% of all in‐patient beds [ 5 , 23 ]. Data regarding daily treatment costs are rare and subject to significant fluctuations, ranging between £1020 ($1248; €1218) and £2720 ($3328; €3247) [ 4 , 23 , 24 , 25 ]. The average daily treatment costs in the non‐COVID‐19 control cohort of our study lie within the range of these previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, 87 studies met the eligibility criteria and were included in this analysis (Fig. 1) [16–102]. The κ value for agreement on full text was excellent (0.90, p <0.01).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study investigating cost-effectiveness using a cohort of critically ill patients, the parameter clearly illustrated an improvement in the efficiency of medical allocation with an increasing survival rate during ICU admission [ 21 , 28 , 29 ]. In another study, cost-effectiveness with total medical cost and quality-adjusted life years was used to estimate the relationship between medical cost and resource use [ 30 , 31 ]. In our study, we demonstrated an improvement in cost-effectiveness as well as a decrease in medical costs per hospitalization and a shortened duration of hospital stay.…”
Section: Discussionmentioning
confidence: 99%